Outpatient use patterns and experiences among diabetic and hypertensive patients in fragile settings: a cross-sectional study from Lebanon. Issue 5 (24th May 2022) - Saleh, Shadi; Muhieddine, Dina; Hamadeh, Randa S; Dimassi, Hani; Diaconu, K; Noubani, Aya; Arakelyan, Stella; Ager, Alastair; Alameddine, Mohamad
Abstract : Objectives: Assess and describe the health service use and delivery patterns for non-communicable disease (NCD) services in two contrasting fragility contexts and by other principal equity-related characteristics including gender, nationality and health coverage. Setting: Primary healthcare centres located in the urbanised area of Greater Beirut and the rural area of the Beqaa Valley. Design: This is a cross-sectional study using a structured survey tool between January and September 2020. Participants: 1700 Lebanese and Syrian refugee patients seeking primary care for hypertension and diabetes. Primary and secondary outcomes: The main outcome is the comprehensiveness of service delivery comparing differences in use and service delivery patterns by fragility setting, gender, nationality and health coverage. Results: Compliance with routine NCD care management (eg, counselling, immunisations, diagnostic testing and referral rates) was significantly better in Beirut compared with Beqaa. Women were significantly less likely to be offered lifestyle counselling advice and referral to cardiologists (58.4% vs 68.3% in Beqaa and 58.1% vs 62% in Beirut) and ophthalmologists, compared with men. Across both settings, there was a significant trend for Lebanese patients to receive more services and more advice related to nutrition and diabetes management (89.8% vs 85.2% and 62.4% vs 55.5%, respectively). Similarly, referral rates were higher among Lebanese refugees compared with Syrian refugees. Immunisation and diagnostic testing were significantly higher in Beirut among those who have health coverage compared with Beqaa. Conclusions: The study discovered significant differences in outpatient service use by setting, nationality and gender to differentials. A rigorous and comprehensive appraisal of NCD programmes and services is imperative for providing policy makers with evidence-based recommendations to guide the design, implementation and evaluation of targeted programmes and services necessary to ensure equity in health services delivery to diabetic and hypertensive patients. Such programmes are an ethical imperative considering the protracted crises and compounded fragility.